مخالفات أبي الفرج الليثي "ت. 331 هـ." الأصولية لأصحابه المالكية: جمعا وتوثيقا ودراسة - آل بوحمامة، علي بن أحمد بن سعيد (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2022)
بدأ الباحث في التمهيد بالترجمة لأبي الفرج الليثي، وبيان مكانته لدى أصحابه المالكية، واهتمامهم بآرائه وتناقلها في كتبهم، وحدد الباحث مجال بحثه في الآراء المنقولة عنه والتي خالف فوها أصحابه المالكية وجمهور الأصوليين، وبعد ذلك درستها دراسة أصولية، وقد أظهر الباحث هذه المخالفات وقارنها بآراء أصحابه المالكية؛ فأبو الفرج يرى بأن المباح مأمور به، وهذا القول مخالف لأصحابه المالكية وجمهور الأصوليين، ويرى بين استصحاب البراءة الأصلية ليس بحجة، وهو قول يخالف فيه أصحابه، ولكنه لم ينفرد به، وإنما وافقه الأبهري، ويرى جواز نسخ القرآن بالسنة المتواترة إلا أن أصحابه خالفوه في الدلول المنقول عن الإمام مالك، ويرى بين الأمر المطلق يقتضي الندب، وهو قول يخالف فوه أصحابه، ولكنه لم ينفرد به، وإنما وافقه ابن المنتاب، ويرى بأن العبرة بخصوص السبب لا بعموم اللفظ، وهو قول يخالف فيه أصحابه، ويرى تقديم المباح على الحاظر حال التعارض، وهو قول يخالف فيه أصحابه، ولكنه لم ينفرد به، وإنما وافقه القاضي عبد الوهاب. The researcher began in the preamble with the translation of Abu al-Faraj al-Laithi, and the statement of his status among his Maliki companions, and their interest in his opinions and transmitted in their books, and the researcher identified the field of his research in the opinions quoted from him, in which his companions disagreed with the Malikis and Abu al-Faraj believes that the permissibility is ordered by him, and this statement is contrary to his Maliki companions and the audience of the fundamentalists, and he believes that the accompaniment of the original innocence is not an argument, which is a statement in which he disagrees with his companions, but he did not single him out, but he agreed with Al-Abhari, and he sees the permissibility of copying the Qur'an in the Sunnah repeated, but his companions disagreed with him in the evidence quoted from Imam Malik, and he believes that the absolute order requires scarring, which is a statement that contradicts it His companions, but he was not unique to him, but Ibn Al-Muntab agreed with him, and believes that the lesson regarding the reason is not the general word, which is a saying in which he disagrees with his companions, and sees the submission of permissibility on the case of conflict, a saying in which his companions disagree, but he was not unique to him, but was approved by Judge Abdul Wahab.
Keywords: الليثي، عمر بن محمد بن عمرو، ت. 331 هـ. -- الفقه الإسلامي -- المذهب المالكية -- القرآن الكريم